IDENTIFYING THE SPACE OF SHIVA’S RUDRA VEENA: A QUEST TO EXPLORE MYTHS, BELIEFS, AND FACTS IN THE DISCOURSE OF THIS ANCIENT MUSICAL INSTRUMENT - Ananya Misra (Arts Academy)
Rudra Veena, an ancient musical instrument is believed to be most widely used in North Indian Classical Music. Being one of the first musical instruments in Hindustani Classical Music, it has a significantly interesting history of its own, which is intertwined with various captivating facts, myths, and beliefs. My goal in this paper is to explore the intricacies involved in the making of this extravagant instrument, the myths and the stereotypes related to it, and the efforts of some prominent Rudra Veena players who have fought with time and defied a change that’s inclined to modern musical taste in the quest to keep the tradition of Rudra Veena alive. In my opinion, it is significant to trace these elements that are now rooted in an unspeakable silence and demand a voice of their own.